Risk factors for corneal monochromatic aberrations and implications for multifocal and extended depth-of-focus intraocular lens implantation - Kanclerz, Piotr; Bazylczyk, Natasza; Przewłócka, Katarzyna; Khoramnia, Ramin; Atchison, David A.; Tuuminen, Raimo (Journal of refractive surgery, 2024)
PURPOSE: To discuss factors influencing corneal aberrations that might influence the optical quality after intraocular lens (IOL) implantation. - METHODS: PubMed and Scopus were the main resources used to search the medical literature. An extensive search was performed to identify relevant articles concerning factors influencing the level of corneal aberrations as of August 27, 2023. The following keywords were used in various combinations: corneal, aberrations, defocus, astigmatism, spherical aberration, coma, trefoil, quadrafoil, intraocular lens, and IOL. - RESULTS: Conclusive evidence is lacking regarding the correlation between age and changes in corneal aberrations. Patients with astigmatism have greater corneal higher-order aberrations than those with minimal astigmatism, particularly concerning trefoil and coma. Increased levels of corneal higher-order aberrations are noted following contact lens wear, in patients with dry eye disease, and with pterygium. Increased higher-order aberrations have been reported following corneal refractive surgery and for 3 months following trabeculectomy; regarding intraocular lens surgery, the results remain controversial. - CONCLUSIONS: Several factors influence the level of corneal higher-order aberrations. Multifocal and extended depth-of-focus IOLs can share similarities in their optical properties, and the main difference arises in their design and performance with respect to spherical aberration. Preoperative evaluation is critical for proper IOL choice, particularly in corneas with risk of high levels of aberrations. [J Refract Surg. 2024;40(6):e420-e434.].
Gesehen am 13.05.2025